Efektivitas Pembelajaran Matematika Menggunakan Model Pembelajaran Core (Connecting, Organizing, Reflecting, Extending) Ditinjau Dari Disposisi Matematis Siswa - Syahrian nur; Madyunus Salayan; Suwarno Ariswoyo (Universitas Muhammadiyah Enrekang, 2020)
This study aims to examine the effectiveness of mathematics learning using the Core learning model in terms of students' mathematical dispositions. Researchers use quantitative research methods by using experimental methods. The experimental method is a method that has two groups or classes, characterized by the treatment (treatment). The population in this study were all students of class VII MTs Negeri 6 Mandailing Natal. The selection of research samples is determined by randomly selecting two classes. The instruments used in data collection consisted of tests and questionnaires. The results showed that there were interactions between the influence of Core learning models with students 'mathematical disposition and also provided an increase in students' mathematical dispositions using the Core learning model. Keywords: Core, Mathematical Disposition, Effectiveness.